Acid Adaptation Impacts Survival and Pathogenicity of Salmonella Enteritidis and Escherichia coli O157:H7 in Orange Juice - Maria Belén Bainotti; Pilar Colás-Medà; Anna Pié-Amill; Inmaculada Viñas; Isabel Alegre (Beverages, 2025)
Pathogenic bacteria surviving acidic conditions in foods pose a persistent public health risk, with acid adaptation potentially enhancing their virulence in low-pH environments like fruit juices. In this study, we hypothesized that foodborne bacteria exhibit enhanced survival and pathogenic potential in fruit juice after undergoing prior acid adaptation. Thus, our aim was to investigate the pathogenic potential and survival of acid-adapted Salmonella Enteritidis and Escherichia coli O157:H7 in orange juice. Cells were acid-adapted by cultivation in a glucose-rich medium, resulting in an increase in bacterial populations from 3.0–3.1 to 8.7–9.0 log10 CFU/mL, compared to non-acid-adapted controls. After 2 days at the common temperature storage of the fruit juices (4 °C), the acid-adapted S. Enteritidis and E. coli survived at higher levels in orange juice compared to non-acid-adapted populations (differences of around 1.7 log units between both). Finally, acid-adapted bacteria showed greater survival during passage through simulated gastrointestinal tract conditions, indicating increased pathogenic potential. Regarding the pathogenic potential, acid-adapted E. coli O157:H7 showed an adhesion capability of around 3.5 times higher in comparison with non-acid-adapted E. coli O157:H7. These results highlight the importance of considering the adaptability of foodborne bacteria to acidic conditions in food safety and security studies.